The Effect of Individual Compounds from Rubus chamaemoruson Hemostasis in vitro - V. G. Luzhanin; A. V. Samorodov; A. K. Whaley; A. O. Whaley; G. P. Yakovlev; I. A. Samylina (Разработка и регистрация лекарственных средств)
Introduction. One of the key tasks of the pharmaceutical industry is the search for new promising compounds – potential drug candidates. Natural objects, especially plants, have long been rich sources of new molecules and are widely used in the global food and pharmaceutical industries. Cloudberry (Rubus chamaemorus L.) is a perennial herb from the Rosaceae family. The fruits and leaves of R. chamaemorus contain a wide variety of polyphenolic secondary metabolites – hydrolysable/condensed tannins and flavonoids. Extracts enriched by polyphenols showed significant antiproliferative activity and inhibition of cell growth, and also induce cell apoptosis. As a result of our previous phytochemical research of R. chamaemorus leaves, five polyphenolic secondary metabolites belonging to the classes of tannins and flavonoids were isolated and characterized.Aim. Screening of previously isolated from R. chamaemorus individual compounds for the hemostasis system in vitro and identification of the most promising compounds for subsequent pharmaceutical development.Materials and methods. Experiments under in vitro conditions were performed on the blood of healthy male donors. The research of the effect on platelet aggregation was carried out according to the Born method on an AT-02 aggregometer (LLC "SPF "Medtech", Russia). Determination of anticoagulant activity was carried out by conventional clotting tests on a Solar CGL 2110 turbidimetric hemocoagulometer (CJSC "SOLAR", Russia). Cytofluorimetric analysis was performed on a NovoCyte instrument (Agilent Technologies, USA).Result and discussion. The influence of the isolated compounds 1–5 on the parameters of activation, platelet aggregation and the coagulation component of hemostasis was studied. At a concentration of 1.0 mg/ml, compounds 1–5 did not affect the fibrinogen concentration and prothrombin time. Compounds 1, 3 and 5 completely suppressed platelet activation at the studied concentrations. Compounds 1 and 3 showed antiaggregation activity comparible to the values of acetylsalicylic acid and are contained in all aqueous and alcoholic extracts of R. сhamaemorus leaves; their quantitative content varies depending on the extraction conditions.Conclusion. Thus, as a result of the screening of individual compounds 1–5 isolated from the leaves of R. chamaemorus their antiaggregating and anticoagulation properties were established. Compounds 1 (4-O-α-L-arabinofuranosylellagic acid) and 3 (quercetin-3-O-β-D-glucuronide) showed antiaggregation activity comparible to that of acetylsalicylic acid, and are the most promising of the studied series of compounds for the subsequent pharmaceutical development of new antiplatelet agents.